Handbook of inorganic chemistry - Wilde, Bernard (NY Research Press, 2015)
This book has been written by experts in the field of inorganic chemistry. The topics discussed in this book cover some of the crucial aspects of inorganic chemistry such as electrochemical activities, characteristic study of various complex compounds, synthesis of compounds and uses of these processes in different fields of science. This book covers the advanced concepts and recent developments in this field. This book aims to serve as a resource guide for students and experts alike.